Konsentrasi Logam Berat Besi (Fe), Mangan (Mn), Tembaga (Cu) pada Perairan Sungai Radda - Hasanuddin; Franita Leonard (Jurnal Penelitian Multidisiplin Ilmu, 2023)
The presence of heavy metal content in waters can indicate the condition of polluted waters so as not to interfere with the sustainability of the ecosystem that occurs in these waters. This study aims to obtain information on the presence of heavy metals Copper (Cu), Iron (Fe) and Manganese (Mn) in Radda river water bodies. This research uses exploratory descriptive research conducted by analyzing the results of water quality measurements. The results of river water quality testing on the parameters of Copper (Cu) obtained results of 0.008 mg/l, Iron (Fe) of 0.027 mg/l, and Manganese (Mn) of 0.007 mg/l show that river water quality does not exceed the quality standards set in Government Regulation of the Republic of Indonesia No. 22 of 2021.